Diferenciação de castas em Inquilinitermes fur (Isoptera, Termitidae) - Silva, Alzair da Costa (2015)
Termitidae family is one of the most both diverse and abundant among the termites and its caste development pattern has an irreversible decision point from the first changes resulting in two strains, one nymphal and other aptera. In this study, it was assessed the patterns of caste development Inquilinitermes fur, a species of Termitidae family which is obligatory inquilines within arboreal nests of Constrictotermes cyphergaster. Twelve nests were collected over a period of one year, with samples taken every 60 days, from October 2011 to August 2012 in a Caatinga area at the Moreira Farm, São João do Cariri, Paraíba. For the analysis of morphometric data, they were used 11 variables including larvae, workers, pre-soldiers, soldiers, nymphs and winged. Principal Component Analysis (PCA) and ANOVA were performed to determine the instars within each lineage and to verify differences among the instars, respectively. The principal results showed that the species has a pattern of caste approximated of the Termitidae family, presenting a nymphal lineage but they have not found the five nymphal instars and another apterous lineage with just one instar for soldier, presoldiers and workers. Sex determinations were made only on workers, soldiers. So, like most studies of Termitinae, we found individuals males and females in the worker caste preceded by two larval instars. Soldiers have also been found males and females, as well as the two species studied Amitermes, which was not found in both sexual dimorphism soldiers as for workers. This pioneering work focused on the castes development patterns of I. fur showed that this species, even though it is obligatory inquilines of C. cyphergaster and has a distinctive life habit, remains the same patterns type of "forked" for the caste differentiation.